Advanced Information Extraction with n-gram based LSI - Guven, Ahmet; Bozkurt, O. Ozgur; Kalipsiz, Oya (WORLD ACAD SCI, ENG & TECH-WASET, 2006)
Number of documents being created increases at an increasing pace while most of them being in already known topics and little of them introducing new concepts. This fact has started a new era in information retrieval discipline where the requirements have their own specialties. That is digging into topics and concepts and finding out subtopics or relations between topics. Up to now IR researches were interested in retrieving documents about a general topic or clustering documents under generic subjects. However these conventional approaches can't go deep into content of documents which makes it difficult for people to reach to fight documents they were searching. So we need new ways of mining document sets where the critic point is to know much about the contents of the documents. As a solution we are proposing to enhance LSI, one of the proven IR techniques by supporting its vector space with n-gram forms of words. Positive results we have obtained are shown in two different application area of IR domain; querying a document database, clustering documents in the document database.
Keywords: Document clustering; Information Extraction; Information Retrieval; LSI; n-gram; Computer Science; Engineering